Natural vulnerability to contamination of the aquifer Alter do Chão in urban area of Manaus, Amazonas, Brazil - Duarte, Miqueias Lima (2019)
The use of underground water resources grows due to population growth and productive activity, increasing the demand for quality water, while growing the risks of its contamination. The present study evaluated the vulnerability to contamination of the Alter do Chão aquifer in the urban area of the municipality of Manaus, with the application of the method GOD (Groundwater occurrence Overall Lithology of the unsaturated zone, Depth of the water table). The use of the method allowed the mapping of differentiated areas in the three classes of vulnerability. The low vulnerability to contamination was predominant (0.41%), followed by the mean vulnerability (0.35%) and high vulnerability to contamination (0.24%). The distribution of the classes of high vulnerability in the study area is a cause for concern, due to the potential contamination associated with the current use and occupation of the soil, also due to the direction of the underground flow.